Fusion of Glutamate Dehydrogenase and Formate Dehydrogenase Yields a Bifunctional Efficient Biocatalyst for the Continuous Removal of Ammonia - Marchini, Valentina; Benítez-Mateos, Ana I.; Roura Padrosa, David; Paradisi, Francesca (Frontiers in Catalysis, 2021)
A novel chimeric protein has been rationally designed, combining the hexameric glutamate dehydrogenase from Clostridium symbiosum with the dimeric formate dehydrogenase from Candida boidinii. The former enzyme consumes ammonia for the reductive amination of α-ketoglutarate using NADH, while the latter biocatalyst regenerates continuously the cofactor. This chimeric fusion opens new perspectives for the detection and the removal of ammonia. The bifunctional biocatalyst has been successfully created, expressed, and then characterized. The two fused protein domains retained identical properties and catalytic activity of the individual enzymes. Additionally, the immobilization on a methacrylate resin optimized the chimeric assembly providing a reusable and stable biocatalyst. This is an example of immobilization of a chimeric enzyme, so that efficiency and sustainability of the process are enhanced. The immobilized chimera could be recycled 10 times retaining still half of the initial activity. Such preparation outperforms the co-immobilized wild-type enzymes in the conversion of 300 mM of ammonia, which could be carried out also in continuous mode.